Functional Outcomes in Dual Plating of Schatzker 5 and 6 Tibial Plateau Fractures - Hussain, Asad Moiz; Muhammad Shoaib,; Najeebullah,; Ahmad Qureshi, Bilal (Indus Journal of Bioscience Research, 2024)
ObjectivesThe present research plan is to assess the functional and radiological outcomes of dual plating in the management of Schatzker type V and VI tibial plateau fractures and compare the technique's efficacy in promoting fracture union and functional recovery of the affected knee joint.Materials and MethodsA comparative prospective controlled clinical study was undertaken in Schatzker type V and VI fractures patients. Both techniques incorporated dual plating, and the results were measured using the KSS and radiographic analysis. Forty consecutive male patients who underwent surgery for hip fracture within the 12 months of the study provided functional recovery assessments before and after surgery.ResultsAccording to the results, the KSS was raised from the preoperative 45 to 85 at the 12-month follow-up. The union rate was 98 %, and the rate of complications was low, with only 8% developing superficial infections. The average range of motion achieved post-operatively of knee flexion was 125 degrees, which proved that adequate restoration of the range of motion was done.ConclusionThe study shows that dual plating is very effective for Schatzker type V and VI tibial plateau fractures. It results in increased union rates, better functional results, and a beneficial risk profile, which makes it advisable in healthcare management